Boulding’s Psychic Capital: The Linking of Individual and Collective Identities - William Walter Bostock (Faculty of Psychology Universitas Gadjah Mada, 2021)
The purpose of this article is to establish that Kenneth E. Boulding, an economist whose work also encompassed many other disciplines, provided a valuable insight within the study of psychology. Boulding observed that while in an economic unit there is a store of financial capital which is necessary for continued existence, also in human nature there is a need for a reserve of psychic capital that is vital for the mental health of the individual and society. Psychic capital does this by providing a link consisting of positive feelings shared between the individual and the larger grouping. Boulding proposed that a coherent body of thoughts, memories, and emotions may be shared between individual and collective minds as shared psychic capital. Finally, some present-day examples are given whereby the consequences of a loss of psychic capital have been observed with particular emphasis on collective depression and suicide.